Kreatifitas Produser dalam Produksi Film Fiksi Pendek Seruah - Utami, Citra Dewi; Petrucciano, Audi (Jurnal Audiens, 2026)
This article examines the creative role of the producer in the production of the short fiction film Seruah. This management study is based on the understanding that the creation of a short fiction film is a dynamic, collaborative process, involving the exchange of creative ideas, creative decision-making, and adjustments to production conditions at every stage. Producers are often understood as solely responsible for managerial and administrative tasks. However, this study demonstrates that producers also play a crucial role in the artistic realm through collaboration with the director and coordination with department heads. This study employed practice-based research as its methodology. Data were collected from observation notes during the production process, archives and documentation of production activities, and the author's reflections. This study employed a practice-based research approach, in which the author was directly involved as a producer in the production process. Findings from the producer's creative role include: during the development stage, aligning emerging ideas with the director's vision; during the pre-production stage, the producer acted as a balancer between artistic needs and budget availability to ensure the production vision was maintained. Furthermore, during the production and post-production stages, the producer acted as a mediator in discussions and thus participated in artistic decision-making. The conclusion of the study indicates that the producer of the short film Seruah has demonstrated his creative role in the creative process through practice-based research.